Parotid gland stem cells: Mini yet mighty. Issue 4 (27th November 2020) - Sari, Sezin Yuce; Yilmaz, Melek Tugce; Elmali, Aysenur; Yedekci, Fazli Yagiz; Yuce, Deniz; Ozyigit, Gokhan; Cengiz, Mustafa; Yazici, Gozde
Abstract: Background: Our aim was to evaluate the correlation between the radiation doses to parotid gland (PG) stem cells and xerostomia. Methods: Patients diagnosed with head and neck cancer (HNC) were retrospectively evaluated, and xerostomia inventory (XI) was applied to these patients. PG stem cells were delineated on the treatment planning CT, and the mean doses to the PG stem cells calculated. Results: The total test score and mean doses to bilateral PGs were significantly correlated ( r = .34, P = .001), and the mean doses to bilateral PG stem cell niches were significantly correlated with the total test score ( r = .32, P = .002). Conclusions: In this study, we found that the mean dose to PG stem cells can predict dry mouth as much as the mean dose to the PG.